Assessment of Demographic Characteristics Among CAD Patients by Ethnicity - Bista, Mamta; Gaudel, Saroj Prasad; Gartoulla, Kshitij; Dhakal Lamichhane, Sunita (NPRC Journal of Multidisciplinary Research, 2024)
Background: This study was carried out to assess the demographic characteristics among CAD by ethnicity.Methods: Retrospective study was performed in (SGNHC) Shahid Gangalal National Heart Centre, Kathmandu, Nepal. Hospital Database of 837 patients were used to gather the information about the disease during one year period. SPSS version 20 was used for statistical analysis.Results: As the hospital lies in the Capital city and Central Region of the country, most of the population 604 (72.2%) had come from Central region, 126 (15.4%) from Western region, 62(7.6%) from Eastern region, 15(1.8%) from Far-western region and 11(1.3%) from Midwestern region.Conclusion: The study examined 837 CAD patients, primarily Brahmin/Chhetris (44.7%), with an average age of 58.6 years and 71.9% being male. Most patients were from Nepal's Central Region.Acute STEMI was the most common diagnosis, particularly among Newars, while NSTEMI and Angina Pectoris were more prevalent in Dalits. Single vessel disease was frequent in Muslims, with Dalits showing higher rates of triple vessel disease, highlighting demographic and regional variations in CAD severity.CAD has been identified as public health priority in Nepal given the current and predicted burden of all forms of heart disease within the country. This study found that there was a diverse distribution in its well-known traditional risk factors among major Nepalese ethnic groups and demographic characteristics.